Retro-engineering the protein sparing effect to preserve n-3 LC-PUFA from catabolism and optimise fish oil utilisation: A preliminary case study on juvenile Atlantic salmon - David Francis; GM Turchini (2017)
Protein has historically been the more expensive macronutrient in aquafeeds. In consideration of this, the implementation of high energy diets for increased protein utilisation is common in modern day aquafeed formulations, evoking what is widely coined as the “protein sparing effect”. However, market forces are changing the cost and availability of raw materials, and oils are now as expensive, if not more expensive, than most protein sources. In light of this, the current study looked to retro-engineer the “protein sparing effect” to test the hypothesis that dietary lipids (in particular omega-3 long chain polyunsaturated fatty acids; n-3 LC-PUFA) could be spared from catabolism by the provision of a high protein diet, manifesting in a more efficient retention/utilisation of these health promoting fatty acids. As such, a case study was implemented in which Atlantic salmon (Salmo salar) were fed a series of iso-energetic diets containing a sliding ratio of dietary protein to lipid, and a fixed concentration of n-3 LC-PUFA. Specifically, these experimental diets were achieved by keeping a constant inclusion of marine derived raw materials (fish meal and fish oil), and varying the relative inclusion of animal by-products (meat and bone meal, blood meal and tallow). Growth performance and feed utilisation parameters as well as tissue fatty acid composition and apparent fatty acid metabolism were assessed. Despite the varying proximate composition of the experimental diets, no significant differences were evident in growth or tissue proximate parameters. Likewise, no conclusive differences were apparent between treatments in relation to the concentration of n-3 LC-PUFA in fillet and whole body samples. However, a remarkable sparing of saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA) from catabolism was apparent and most certainly attributable to 1) the reduced dietary supply of these nutrients, and 2) the preferential utilisation of excess dietary protein for energy production. The results achieved ...